Learning Environmental Rights, Finding Green Future: The Road to Ecojustice - Muhammad Akib; . Fathoni (UBL, 2013)
This paper will make a reconstruction of legal environmental paradigm and find the alternativeparadigm which sees the environment as a unity with human being. The debates of environmental rightsoffer new perspective on rights and environmental issues. The carelessness of sustainable environmentoften occur when the state apply the environmental regulations or policies.Nowadays, the thought of “ecojustice”—environmental justice—has been rapidly developed.Otto Sumarwoto said about “Our Common Future” (Otto, 1991), Jimly Asshiddiqie said about “GreenConstitution” (Jimly, 2009), and Fritjof Capra could say the same in “Green Politics: The GlobalPromise” (Capra, 1984). They make a sense that environmental protection is insufficient if it does notinclude the consideration of whole life, including present and future, that Environmental Rights is a roadto Intergenerational Justice.In developing country such as Indonesia, the development activities cause environmentaldamages. These conditions became worse in the autonomy era (since 2001) until present day, whichenvironmental institution become weak in environmental law enforcement. As examples are Buyat BayCase by Newmont Minahasa Raya, Ltd. (2004); and illegal logging by Adelin Lis (2007). These problemsshould be solved by beginning with an examination of the notion of rights to the environment and to theidentification of such rights in formulation of regulations and policies